DISCRESSION OF THE SAMBAS RESORTS POLICE IN THE IMPLEMENTATION OF ADMINISTRATIVE LAW PERSPECTIVE INVESTIGATION - Tamrin Muchsin; Sri Sudono Saliro; Nahot Tua Parlindungan Sihaloho; Sardjana Orba Manullang (Universitas Muhammadiyah Ponorogo, 2020)
It is still found that investigating officers do not have an S1 degree or equivalent in thejurisdiction of the Sambas Resort Police as mandated in PP No. 58 of 2010 concerningAmendments to Government Regulation Number 27 of 1983 concerning theImplementation of KUHAP article 2A paragraph (1) letter a. If the requirements ofinvestigators are not fulfilled, there will automatically be limits of authority, includingthe inability to issue investigation orders, detention warrants and other administrativeletters. This study used a qualitative method with juridical empirical research. Toobtain accurate data, purposive sampling technique was used, and primary datacollection by conducting in-depth interviews. The research results found, among others:first, discretion regarding the administration of investigations in the jurisdiction of theSambas Resort Police for the Sambas District Police who do not have investigatingofficers who meet the requirements, is then taken over by the Head of the CriminalInvestigation Unit as the supervisor of the integrated criminal investigation function.Second, the impact of an integrated investigation administration causes the time tocarry out investigations to be slow due to the long distance between the Sector Policeand the Resort Police.